Introduction of General Distributions on Sphere and Torus in View of Time Series Spectra - Masanobu Taniguchi; Yujie Xue (Statistica)
There are various fields where observations are taken on directions in three dimensions, e.g., sphere and torus. Herewe will introduce a very general family of distributions on sphere and torus by use of time series spectra, which includes a lot of proposed classical one as special cases. Because time series spectra can be described by a lot of famous parametric models, e.g., AR, ARMA etc., we can develop the systematic model selection in this field by use of AIC, BIC, etc. Applications are very wide.